Introduction - Gorelick, Nathan (Filozofski vestnik, 2025)
This article is the editorial introduction to a special issue of Filozofski Vestnik dedicated to Joan Copjec’s 1994 book Read My Desire: Lacan Against the Historicists. It proposes that an enduring resistance to Copjec’s insights across the theoretical humanities must be understood as a symptom of the radical shift in thinking the book provokes, dis-guised as a proud defense of the illiteracy of desire Copjec indicts. Tracking this proud illiteracy to its origins in the intellectual fallout from the 1968 student revolts in Paris, the author argues that returning to Read My Desire now, thirty years since its initial publication, can inform an engagement with student radicalism, and youth in revolt more generally, that is ethically responsive to the political and social exigencies of the present. The article concludes with a summary of the issue’s other contributions and the ways in which they each introduce novel readings of Read My Desire that demon-strate the book’s lasting impact and reiterate its still-unread. potential.
Keywords: Foucault, Michel; Lacan, Jacques; psihoanaliza; psychoanalysis